Ex Vivo Prediction of Comprehensive Coagulation Potential Using Simulated Blood Concentrations of Emicizumab in Patients with Acquired Hemophilia A - Takeyama, Masahiro; Furukawa, Shoko; Yada, Koji; Ogiwara, Kenichi; Shimonishi, Naruto; Nakajima, Yuto; Mizumachi, Kuniyoshi; Noguchi-Sasaki, Mariko; Shima, Midori; Nogami, Keiji (Thrombosis and Haemostasis, 2021)
Introduction Emicizumab prophylaxis improves coagulation function in congenital hemophilia A, regardless of inhibitor presence. We recently reported that emicizumab enhanced the coagulant potentials, ex vivo, in plasmas from patients with acquired hemophilia A (PwAHAs) at diagnosis. However, coagulant effects of emicizumab in PwAHAs during the clinical course remain unclear.Aim To assess ex vivo coagulant effects of emicizumab in PwAHAs during the clinical course.Methods/Results Blood samples were obtained from 14 PwAHAs on (median) days 0 and 6 during a severe-bleeding phase, and days 27 and 59 during a reduced-bleeding phase with elevated endogenous factor VIII (FVIII) and decreased inhibitor titers. If administered a single dose of 3 or 6 mg/kg, or two doses at 6 mg/kg followed by 3 mg/kg, estimated plasma emicizumab concentrations (10/5/2.5, 20/10/5, and 30/15/7.5 µg/mL on days 0–7/30/60, respectively) could be used to represent potential changes, based on the half-life (T1/2: ∼30 days). Emicizumab concentrations that covered maximum plasma concentrations of each dosage were used for spiking on day 0. Ex vivo addition of estimated emicizumab to PwAHA's plasma containing endogenous FVIII and/or inhibitor, without and with recombinant (r)FVIIa administration during immunosuppressive therapy, increased the calculated Ad|min1| values, assessed by clot waveform analysis, and their coagulant potentials were below normal levels. Rotational thromboelastometry revealed that ex vivo emicizumab addition resulted in the further improvement of coagulant potentials in whole bloods when combined with rFVIIa administration.Conclusion Based on ex vivo and in vitro data, emicizumab has the potential to be effective in clinical situations for PwAHAs.
Keywords: bispecific; acquired hemophilia A; autoantibodies; pharmacokinetic; coagulation